(x+5)/3=2-(x+6)/2

Simple and best practice solution for (x+5)/3=2-(x+6)/2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+5)/3=2-(x+6)/2 equation:



(x+5)/3=2-(x+6)/2
We move all terms to the left:
(x+5)/3-(2-(x+6)/2)=0
We calculate fractions
x/()+(-(2-(x+6)*3)/()=0
We calculate terms in parentheses: +(-(2-(x+6)*3)/(), so:
-(2-(x+6)*3)/(
We multiply all the terms by the denominator
-(2-(x+6)*3)
We calculate terms in parentheses: -(2-(x+6)*3), so:
2-(x+6)*3
determiningTheFunctionDomain -(x+6)*3+2
We multiply parentheses
-3x-18+2
We add all the numbers together, and all the variables
-3x-16
Back to the equation:
-(-3x-16)
We get rid of parentheses
3x+16
Back to the equation:
+(3x+16)
We get rid of parentheses
x/()+3x+16=0
We multiply all the terms by the denominator
x+3x*()+16*()=0
We add all the numbers together, and all the variables
x+3x*()=0

See similar equations:

| 4(x-6)-(x+8)=x+10 | | x2+4x+2=0 | | 90(4x-6)=180 | | 5x2+15=3x2+65 | | 2+x=22 | | 9y-27=6(y-2) | | 18x-5=-9(x-4) | | x^+3x-27/4=0 | | (x+)4+(4x)+(10x-10)=288 | | 2x^2+40=140 | | 4x+1=9+4x+1 | | 4x-37=23-6x | | -4y=-7 | | 2+6x=-5 | | K/5+3-3k=6 | | 6p+11=1+8p | | |x-7|=|2x-1| | | 4/8=r/4 | | 80+0.60m=50+0.90m | | 3n+2+n=2(2n+1)5n+7 | | 12a=5a+42 | | 15x+4=11x+15 | | (3+3)(6+1x)=50-2.5(x+3) | | 7-4y=0 | | 4x+8=7.2+x | | 5y-3(5-2y)=-25 | | 4(y-4)=4+y-8 | | 4x+1=9+4+1 | | 9z-2z-8=62 | | ((b+4)+b+(b-1))/3=97 | | 10w^2=19w+5 | | 8p+160=40p |

Equations solver categories